Pengaruh Edukasi Kesehatan Tentang Perawatan Tali Pusat Terhadap Perilaku Ibu Post Partum Di Wilayah Kerja Puskesmas Kaiely Kabupaten Buru - Syahfitrah Umamity; Ellen Lombonaung; Iswandi Fataruba (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Sometimes umbilical cord infections occur because young mothers are unaware of the need to provide umbilical cord care to their babies after giving birth. The umbilical cord, a type of connective tissue, holds the placenta and foetus together. The umbilical cord functions as a source of life for the foetus while it is in the womb. Umbilical cord care is a procedure for handling the umbilical cord in a sterile, clean, and dry manner to avoid infection. The aim of the research is to find out how health education on umbilical cord care influences the behaviour of postpartum mothers in the work environment at the Kaiely Community Health Centre, Buru Regency, in 2024. This research uses a pre-experimental research strategy. Total sampling was used as the sampling technique. We used the Wilcoxon test to analyze the data. The research findings showed a p-value of 0.001 when compared with the significance level (p-value <0.05), thus approving Ha. This shows that health education regarding correct umbilical cord management influences the behaviour of postpartum mothers in the operational area of the Kaiely Community Health Centre, Buru Regency. Based on the research conclusions, postpartum mothers fall into the poor knowledge category, negative attitude category, action not implemented, poor pre-test and post-test behaviour category, and action not taken. behaviour is classified as very good, and the behaviour of postpartum mothers at the Kaiely Community Health Centre, Buru Regency, is influenced by health education about umbilical cord care.